The Municipal People’s Council: How wides pread are the participatory mechanisms? - Houchat, Fouzia (Journal of Human Sciences, 2020)
The constitutional of 2016 has enshrined new concepts that did not exist before including participatory democracy, especially at the local level, which allows the participation of civil society in its various components with the citizen in the public management process, by participating in public decision-making at the local level, because governance of local administration requires the development of an effective participatory policy.However, the process of transforming the Municipal People’s assembly into a reality that is consecrated on the ground requires the use of various mechanisms that guarantée citizen participation in the decision process.In the absence of laws that would provide local authorities with mechanisms of participatory democracy, Algeria applied a unique experiment known as the Capdal project at the level of tem municipalities, and each municipaety has different characteristics.